Light deflection method and device based on strontium barium niobate crystal with gradient components

By preparing strontium barium niobate crystals with gradient components and using their secondary electro-optical effects, the problems of complex structure and low deflection efficiency of existing electro-optical deflection devices are solved, and a more efficient and flexible beam deflection effect is achieved.

CN119902401AActive Publication Date: 2025-04-29NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510093874.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing electro-optical deflection devices have complex structures, difficult processing and low deflection efficiency.

Method used

Strontium barium niobate crystals with gradient components were prepared, beam deflection was achieved using its secondary electro-optical effect, SrxBa1-xNb2O6 crystals were grown by lifting method, component gradient was controlled, and device performance was optimized using a bilayer metal electrode and a rapid annealing process.

Benefits of technology

It realizes a simpler structure, smaller size and higher deflection efficiency, and improves the maximum deflection angle to mrad level, expanding the application range of electro-optical deflection devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119902401A_ABST
    Figure CN119902401A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectric functional crystal materials, in particular to a light deflection method and device for strontium barium niobate crystals with gradient components. The method comprises the following steps: firstly, growing an SBN crystal with a component gradient along a [001] direction by adopting a Czochralski method, cutting a cuboid optical wafer according to the crystal orientation, preparing an ohmic contact double-layer metal electrode on a polished (001) surface by adopting a magnetron sputtering method, controlling the temperature of the crystal to be 3-5 DEG C below the effective Curie temperature, and carrying out incidence along the [100] or [001] direction, an electric field is applied to the crystal in the component gradient direction, light deflection can be achieved at the emergent end, and the maximum deflection angle can reach 9.6 mrad under the voltage of 800 V / mm. Compared with a traditional deflector based on the linear electro-optical effect, the method can obtain a larger deflection angle and remarkably reduce the device size and structural complexity, and is suitable for the fields of high-speed random scanning, display, laser processing, space optical communication and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optoelectronic functional crystal materials, and in particular to a light deflection method and device based on barium strontium niobate crystals with gradient components. Background Art

[0002] A beam deflector, also known as a beam scanner, is a device that changes the propagation direction of a beam in space according to a certain rule. Beam deflection technology is widely used in display, sensing, optical storage, laser printing, microscopic imaging, laser processing, laser radar and space optical communication.

[0003] At present, the beam deflection technology can be divided into two types: mechanical and non-mechanical. The traditional mechanical deflection usually adopts a rotating mirror (CN104749565B), a galvanometer (CN111289955B) or a micro-electromechanical (MEMS) scanning mirror (CN109085600B). The inertia of the mechanical components leads to low scanning frequency and stability. The non-mechanical beam deflection technology usually adopts acousto-optic (AOD) (CN107850796B) or electro-optic deflection device (EOD) (CN110543035B), which has the advantages of small device size and easy high-frequency scanning. In particular, the electro-optic deflector has more advantages than the acousto-optic deflection in terms of deflection angle and response speed, and can better meet the application requirements in the field of high-speed random scanning.

[0004] The electro-optic deflector uses the electro-optic effect to change the propagation direction of a light beam in space, that is, by applying an external voltage, the refractive index of the crystal changes under the action of the electro-optic effect, thereby changing the propagation direction of the light. Early electro-optic deflection devices were prism-shaped (Lee T, Zook J. Light beam deflection with electrooptic prisms [J]. IEEE Journal of Quantum Electronics, 1968, 4 (7): 442-454.). The advantages of this prism-structured electro-optic deflector are that it can achieve fast response and continuously changing deflection. However, since the deflection only occurs at the interface between two materials, a plurality of prisms need to be used to form an array to obtain a larger deflection angle, resulting in a large device size, complex structure, and a high driving voltage, which limits its application.

[0005] Another type of electro-optic deflection is based on the deflection of a light beam caused by a refractive index gradient perpendicular to the light beam propagation direction. Usually, a gradient electric field is created inside the crystal using special-shaped electrodes, such as a deflector with a four-electrode structure (Zhao Zhuo, Chen Ming, Liu Xiangnan, et al. Electro-optic deflector with a four-electrode octagonal structure [J]. Laser & Optoelectronics Progress, 2020, 57(15): 199-204.). A gradient refractive index distribution is formed perpendicular to the light beam propagation direction. During the propagation of the light beam, it will deflect towards the direction where the refractive index gradient increases, and the deflection angle can be controlled by an applied voltage. The advantage of gradient refractive index deflection is that the light beam deflection does not only occur on the surface of the material but accumulates continuously during the propagation of the medium. Compared with a deflector with a prism structure, a larger deflection angle can be obtained using a shorter optical path and a smaller-sized device. However, due to the complex shape of the components of this deflector, it brings certain difficulties to processing, and it is limited by the electro-optic coefficient of the electro-optic material, resulting in a low deflection efficiency. Taking the deflector with a four-electrode structure proposed by Zhao Zhuo et al. as an example, its deflection efficiency is only 0.312 μrad / V.

[0006] The above two deflectors based on the prism structure and the four-electrode structure (gradient electric field) both rely on the refractive index change caused by the electro-optic effect. The electro-optic effect can be divided into the linear electro-optic effect and the quadratic electro-optic effect according to the relationship between the refractive index change and the applied electric field. Since the quadratic electro-optic effect of general crystals is much smaller than the linear electro-optic effect, currently commercially available electro-optic deflection devices are all based on the linear electro-optic effect, and the quadratic electro-optic effect is rarely utilized. Summary of the Invention

[0007] Aiming at the above deficiencies of the prior art, the present invention prepares a strontium barium niobate crystal with a gradient composition, and proposes a light deflection method and device based on the quadratic electro-optic effect of a tetragonal strontium barium niobate crystal, solving the problems of complex structure, difficult processing, and low deflection efficiency of traditional electro-optic deflection devices.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] Using the Czochralski method to grow a Sr x Ba 1-x Nb2O6 crystal (SBN crystal), the initial raw material ratio should deviate from the solid-liquid congruent point (i.e., Sr content x = 0.61, at this time the Sr / Ba content in the raw material is the same as that in the crystal). To ensure that the crystal has a large composition gradient, the range of the initial raw material molar ratio should be: 0.65:0.35 < SrCO3:BaCO3 < 0.79:0.21, and the corresponding composition gradient (composition change per unit length) Δx / l of the obtained crystal in the growth direction > 10 -3 / mm.

[0010] The above-mentioned SBN crystal with component gradient is used and processed into a rectangular parallelepiped wafer, each surface corresponds to the (100), (010) and (001) planes of the crystal respectively, the light-transmitting surface and the electrode-plated surface are optically polished, metal electrodes are plated on two planes perpendicular to the growth direction (i.e., the (001) plane), and light is transmitted along the

[100] or

[010] direction (i.e., incident perpendicular to the (100) plane or the (010) plane). Before the light beam enters the crystal, a linear polarizer is used to convert the incident light into linearly polarized light polarized along the

[001] direction, and an electric field is applied to the crystal along the

[001] direction, so that the light beam can be deflected at the crystal output end.

[0011] Furthermore, since the crystal itself has a composition gradient, that is, the components at different positions in the crystal are different, the Curie temperature at different positions in the crystal is different. The temperature corresponding to the maximum value of the dielectric constant can be read out using a dielectric thermometer, which we call the "effective Curie temperature" (T c When the SBN crystal is used as an electro-optical deflection element, its temperature usually needs to be controlled within a range of 3 to 5°C below the effective Curie temperature. The temperature control accuracy is ±0.1°C, and the temperature control method uses TEC semiconductor temperature control technology.

[0012] Furthermore, since SBN crystals are usually grown in a growth furnace with a nitrogen atmosphere, a large number of oxygen vacancies will be formed in the crystals due to insufficient oxygen during the high-temperature growth process, making the crystals appear dark blue. In order to improve their transmittance and make them more suitable for optical applications, they need to be annealed in a high-temperature oxygen atmosphere to reduce their oxygen vacancy defects so that the crystals become light yellow or nearly transparent. The annealing temperature is 1200°C-1300°C, the constant temperature time is 12-24 hours, and the heating and cooling rate is 100-200°C / h.

[0013] Furthermore, since barium strontium niobate crystals are in the ferroelectric phase below the Curie point, theoretically, the electro-optic effect of the crystal should be a linear electro-optic effect (the secondary electro-optic effect is relatively weak). However, we have found through experimental research that tetragonal SBN crystals exhibit a secondary electro-optic effect before polarization treatment. This is because although each ferroelectric domain inside the SBN crystal has spontaneous polarization and exhibits a linear electro-optic effect, the linear electro-optic effects of different ferroelectric domains cancel each other out due to different orientations, and the secondary electro-optic effect is manifested externally. Theoretical and experimental studies have shown that in SBN crystals with gradient components, the electro-optic deflection angle based on the secondary electro-optic effect is much larger than the deflection based on the linear electro-optic effect. Therefore, in order to obtain a larger deflection angle, when tetragonal SBN crystals are used for electro-optical deflection, they cannot be polarized (that is, they cannot be transformed into single-domain crystals through high-voltage polarization).

[0014] Furthermore, since the unpolarized SBN crystal is easily polarized into a single-domain structured crystal under the action of an applied voltage when used as an electro-optical deflection device, which causes the quadratic electro-optical effect to be transformed into a linear electro-optical effect and causes the electro-optical deflection angle to attenuate, in order to avoid the attenuation of the deflection angle caused by the polarization effect of high voltage, the maximum deflection voltage of the electro-optical deflection should be less than 800V / mm (the length here is the thickness of the crystal in the direction of the electric field).

[0015] Furthermore, in order to reduce the energy loss of the electrode contact surface and improve the device performance and working stability, it is usually necessary to form an ohmic contact between the SBN crystal and the metal electrode. For this reason, we chose to plate a double-layer electrode on the surface of the SBN crystal. According to the relevant theory of work function, SBN crystal is an n-type semiconductor material. To form an ohmic contact electrode, the work function of the selected metal electrode must be smaller than the work function of the SBN crystal, that is, it is easier to form an ohmic contact on the surface of the SBN crystal by selecting a metal with a lower work function. After theoretical and experimental screening, the electrode material of the inner layer in contact with the crystal is one of Al, Ti or Ag, and the electrode material of the outer layer in contact with the air is one of Au or Pt. The outer electrode is used as a protective electrode to prevent the inner electrode from being oxidized and corroded, avoid thermal damage and physical damage, ensure the stability of electrical performance, and extend the life of the device.

[0016] Furthermore, the double-layer metal electrodes are coated on the surface by magnetron sputtering. For the inner electrode, if the film layer is too thin, it is difficult to ensure ohmic contact, and if the film layer is too thick, it is easy to introduce a large impedance at high frequency. The thickness of the inner electrode is usually 50-150nm; for the outer electrode, if the film layer is too thin, its protective effect will be weakened, and if the film layer is too thick, it is easy to cause waste of precious metal materials. The thickness of the outer electrode is usually 100-200nm.

[0017] Furthermore, after the electrode sputtering is completed, in order to further promote the interface reaction between the electrode and the crystal, reduce the contact barrier and reduce the contact resistance, the crystal needs to be rapidly annealed again (secondary annealing). The reason for using rapid annealing instead of conventional annealing is that rapid annealing can effectively limit the excessive diffusion of metal under high temperature conditions. The annealing temperature is 300-500°C, the constant temperature time is 5-10 minutes, the heating time is usually 5-30 seconds, and the annealing atmosphere is nitrogen or argon.

[0018] The beneficial effects of the present invention are:

[0019] (1) By adopting the method of growing crystals in a small crucible and utilizing the non-uniform melting characteristics of SBN crystals when they deviate from the isotropic point, SBN crystals with a specific composition gradient along the growth direction are prepared, and beam deflection is achieved. Compared with the electro-optical deflector with a cascade prism structure or a quadrupole structure, the structure is simpler and the device size is smaller.

[0020] (2) A significant secondary electro-optic effect was found in unpolarized SBN crystals, and theoretical and experimental studies showed that the deflection angle based on the component gradient and the crystal secondary electro-optic effect is much larger than the deflection of the linear electro-optic effect. The maximum deflection angle is increased from the urad level of the linear electro-optic deflection device to the mrad level. This proposal provides a new implementation scheme for the design of electro-optic deflection devices, and the increase in the deflection angle also greatly expands the application range of electro-optic deflection devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 The composition change rules of melt and crystal during the growth process are shown by using the binary system phase diagram of SBN crystal;

[0023] Figure 2 is the transmittance of SBN crystal before and after the first high-temperature annealing;

[0024] Figure 3 The SBN crystal is a SBN crystal with a gradient composition grown by the Czochralski method;

[0025] Figure 4 is the composition uniformity of SBN crystal in (001) and (100) directions;

[0026] Figure 5 The IV characteristic curves before and after rapid annealing when using Ag+Au electrodes;

[0027] Figure 6 The IV characteristic curves before and after rapid annealing when using Ti+Au electrode;

[0028] Figure 7 The IV characteristic curves before and after rapid annealing when using Al+Pt electrode;

[0029] Figure 8 This is a schematic diagram of the SBN crystal electro-optical deflection system;

[0030] Fig. 9 is the dielectric temperature spectrum of SBN crystal with composition gradient;

[0031] Fig.10 The deflection spot position of the SBN electro-optical deflection device under different voltages;

[0032] Fig.11is the deflection angle of the SBN electro-optical deflection device under different voltages;

[0033] Fig.12 It is a Mach-Zehnder interferometer system used to measure the secondary electro-optic coefficient of SBN;

[0034] Fig.13 This is a comparison diagram of the interference light intensity signal and the applied voltage signal waveform measured by the Mach-Zehnder interferometer system;

[0035] Fig.14 Schematic diagram of the principle of electro-optical deflection based on gradient components. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0037] Example 1: Composition gradient SBN crystal growth (initial raw material molar ratio SrCO3:BaCO3=0.73:0.27)

[0038] Figure 1 is the binary system phase diagram of SBN crystal. To obtain SBN crystal with composition gradient, we set the initial ratio of raw materials to the left of the solid-liquid isotope point ( Figure 1 In the embodiment of the present invention, due to the non-constant melting characteristics of crystal growth (i.e., the components of the melt and the crystal are different), during the crystal growth process, the melt component will move from point A to point B, and the corresponding crystal component will move from a to b, thereby obtaining a crystal with a component gradient along the crystal growth direction. In order to obtain a crystal with a larger component gradient, the method of "growing crystals in a small crucible" is usually used. In all embodiments of the present invention, the crucible size used is an iridium crucible of φ50mm×50mm, and the size of the grown crystal is not less than φ20mm×20mm.

[0039] The crystals were grown by the Czochralski method. The experimental raw materials were SrCO3, BaCO3 and Nb2O5 powders with a purity of 4N level. The materials were mixed in the ratio of SrCO3:BaCO3:Nb2O5=0.73:0.27:1 and mixed in a mixer for 48 hours to make the powders fully mixed. In order to form polycrystalline materials more fully, we pre-sintered them twice in a muffle furnace. The first pre-sintering temperature was 900℃ for 36 hours. Then the polycrystalline materials pre-sintered for the first time were placed in an agate crucible. Grind into powder and carry out second pre-sintering at 1300°C for 36h. After the pre-sintering, place the powder in an iridium crucible and then grow it in a growth furnace under a nitrogen atmosphere. Cool down from 1465°C, with a pulling speed of 1mm / h and a rotation speed of 3 / rpm. After more than 70 hours, a transparent blue-black SBN crystal is obtained. Then, annealing is carried out in a muffle furnace at 1200°C for 24h. Finally, a light yellow or nearly colorless and transparent SBN crystal is obtained.

[0040] We measured the transmittance of SBN crystals at different wavelengths before and after annealing. The results are as follows: Figure 2 As shown in the figure, the transmittance of the SBN crystal after annealing (dashed line) is significantly higher than that before annealing (solid line), which indicates that the annealing treatment effectively improves the optical properties of the crystal, especially in the wavelength range of 400-500nm. After annealing, the transmittance rises rapidly from a low value and is much higher than that before annealing. This is mainly due to the presence of oxygen vacancies before annealing, which makes the crystal blue-black and causes strong absorption in the 400-500nm band. Oxygen annealing effectively reduces oxygen vacancy defects, so the annealing improves the transmittance of 400-500nm more significantly.

[0041] Figure 3 (a) is the SBN crystal with composition gradient that we grew. The length along the growth direction is 21 mm and the maximum diameter is 25 mm. Figure 3 (b) Cut a 10mm×10mm×1mm wafer in the direction shown in FIG. Figure 3 (c) As shown. The surface component distribution was measured using EPMA-8050G electron probe technology, and the Sr x Ba 1-x The composition distribution of Nb2O6 crystal along the (100) and (001) directions ( Figure 4 ). The crystal composition does not change much in the (100) direction, but there is a composition gradient in the growth direction, i.e., the (001) direction. The Sr content gradually decreases along the growth direction (001). The composition gradient in the range of l = 10 mm in the (001) direction is calculated to be Δx / l = 0.0015 mm -1 .

[0042] Example 2: Composition gradient SBN crystal growth (initial raw material molar ratio SrCO3:BaCO3=0.65:0.35)

[0043] The crystal was grown by the Czochralski method, the molar ratio of the raw materials was SrCO3:BaCO3:Nb2O5=0.65:0.35:1, the raw material purity was 4N grade, the initial cooling temperature for crystal growth was 1490°C, the annealing temperature was 1250°C, and the other mixing, pre-sintering, crystal growth and annealing process parameters were basically the same as those in Example 1. A 10mm×10mm×1mm wafer was cut from the final crystal, and its component gradient within the range of l=10mm in the (001) direction was measured to be Δx / l=0.0012mm -1 .

[0044] Example 3: Composition gradient SBN crystal growth (initial raw material molar ratio SrCO3:BaCO3=0.79:0.21)

[0045] The crystal was grown by the Czochralski method, the molar ratio of the raw materials was SrCO3:BaCO3:Nb2O5=0.79:0.21:1, the raw material purity was 4N grade, the initial cooling temperature of the crystal growth was 1460°C, the annealing temperature was 1300°C, and the other mixing, pre-burning, crystal growth and annealing process parameters were basically the same as those in Example 1. A 10mm×10mm×1mm wafer was cut from the final crystal, and its component gradient within the range of l=10mm in the (001) direction was measured to be Δx / l=0.001mm -1 .

[0046] Example 4: Preparation of SBN crystal ohmic contact electrode (Ag+Au double-layer electrode)

[0047] In order to reduce the energy loss at the electrode contact surface and improve the device performance and working stability, it is necessary to form an ohmic contact between the SBN crystal and the metal electrode. We chose to plate a double-layer electrode on the surface of the SBN crystal. The inner electrode material in contact with the crystal is Ag, and the outer protective electrode material is Au. The double-layer electrodes are both plated using magnetron sputtering technology.

[0048] A wafer with a size of 3.8mm×3mm×1mm was processed from the native crystal (after annealing) obtained in Example 1, wherein the two planes of 3.8mm×3mm were (001) planes. The two planes were first polished and then electrode-plated. Before electrode plating, the SBN crystal was ultrasonically cleaned and purged with nitrogen. A magnetron sputtering apparatus equipped with dual targets was used for film coating. The crystal temperature was first heated to 70°C, bias sputtering was turned on to remove impurities on the surface of the crystal, and then DC sputtering was used to sputter a layer of Ag metal film with a thickness of 50nm on the surface of the crystal, and then a layer of Au metal film with a thickness of 100nm was sputtered to form a double-layer metal film electrode. The equipment parameters during the sputtering process were set to: argon gas flow rate of 18sccm, DC power supply power of 400W, and chamber pressure of 0.9Pa during sputtering. After sputtering, it was naturally cooled to room temperature. The sample was turned over and the other side was sputtered using the same process to obtain an SBN optical element with double-sided Ag+Au electrodes.

[0049] In order to further optimize the contact characteristics between the electrode and the semiconductor material and reduce the contact resistance, we performed rapid annealing on the SBN wafer after sputtering. We used the Nobadi NBD-HR1200-110TI rapid annealing furnace, placed the electrode-plated SBN crystal, evacuated the chamber and then introduced nitrogen. The heating time was 30 seconds, the annealing temperature was 450°C, and the annealing time was 8 minutes. After the annealing was completed, it was naturally cooled to room temperature to form an electro-optical element with an ohmic contact electrode.

[0050] Figure 5 The IV characteristic curves of the SBN crystal before and after the secondary annealing are generally considered to be ohmic contacts if the IV curve shows linear characteristics, and Schottky contacts if it shows nonlinear characteristics. Figure 5 It can be seen that before annealing, when the applied voltage is small, the IV curve is nonlinear, and then gradually turns into approximately linear with the increase of voltage. After annealing, the IV curve is linear in the entire range. It can be seen that the ohmic contact characteristics between the SBN crystal and the electrode are significantly improved by rapid annealing.

[0051] Example 5: Preparation of SBN crystal ohmic contact electrode (Ti+Au double-layer electrode)

[0052] First, a wafer of the same size and crystal orientation was processed in the same manner as in Example 4, and then a layer of Ti metal film with a thickness of 150 nm was first plated on the surface of the SBN crystal by magnetron sputtering technology, and then a layer of Au metal film with a thickness of 120 nm was plated. The other sputtering process parameters were the same as in Example 4. Then, the SBN wafer after sputtering was rapidly annealed, with an annealing temperature of 500°C, a constant temperature time of 10 minutes, a heating time of 20 seconds, an annealing atmosphere of argon, and the other annealing parameters being the same as in Example 4. The IV characteristic curves before and after annealing were compared, as shown in FIG. Figure 6The IV curve after annealing shows a linear characteristic, indicating that a relatively reliable ohmic contact electrode is formed after rapid annealing.

[0053] Example 6: Preparation of SBN crystal ohmic contact electrode (Al+Pt double-layer electrode)

[0054] First, a wafer of the same size and crystal orientation was processed in the same manner as in Example 4, and then a 100 nm thick Al metal film was first deposited on the surface of the SBN crystal by magnetron sputtering technology, and then a 200 nm thick Pt metal film was deposited. The other sputtering process parameters were the same as in Example 4. Then, the sputtered SBN wafer was rapidly annealed, with an annealing temperature of 300°C, a constant temperature time of 5 minutes, a heating time of 5 seconds, an annealing atmosphere of argon, and the other annealing parameters being the same as in Example 4. The IV characteristic curves before and after annealing were compared, as shown in FIG. Figure 7 The IV curve after annealing shows a linear characteristic, indicating that a relatively reliable ohmic contact electrode is formed after rapid annealing.

[0055] Example 7: Electro-optical deflection based on SBN composition gradient (using a composition gradient of 0.0015 mm -1 Crystals)

[0056] SBN electro-optical deflection experimental device Figure 8 As shown in (a), a wafer with a size of 3.8 mm × 3 mm × 1 mm was processed from the original crystal (after annealing) obtained in Example 1 ( Figure 8 b), whose component gradient is 0.0015 mm -1 , Ag+Au double-layer electrodes were plated on the two (001) surfaces using the method of Example 4, and then the dielectric temperature spectrum was measured ( Fig. 9 ), and its effective Curie temperature is Tc = 65°C. The crystal temperature is controlled at 4 degrees below the Curie point, i.e. 61°C, using a TEC temperature control device. The incident light is a 632.8nm He-Ne laser, which is converted into vertically polarized light polarized along the

[001] direction by a polarizer and incident perpendicular to the (100) surface of the crystal. The voltage signal generated by the signal generator is applied to the crystal along the z direction after passing through a high-voltage amplifier. By changing the voltage applied to the crystal, the movement of the light spot can be observed on the receiving screen. A beam quality analyzer (Thorlabs PDA100A2) is used to record the light spot position under different voltages ( Fig.10 ), the distance from the crystal output end to the receiving surface of the beam quality analyzer is 50 mm, from which the deflection angle under different voltages can be calculated, such as Fig.11The midpoint curve is the result obtained by measurement and calculation. It can be seen that the electro-optical deflection angle increases approximately in a parabolic law with the increase of the applied voltage. When the voltage reaches 800V / mm, the deflection angle reaches saturation (the maximum deflection angle is 10mrad). If the voltage continues to increase, the deflection angle will decrease. This is because the unpolarized SBN crystal is easily polarized into a single-domain structure crystal under the action of the applied voltage, which causes it to change from a quadratic electro-optic effect to a linear electro-optic effect and causes the attenuation of the electro-optical deflection angle. In order to avoid the attenuation of the deflection angle caused by the polarization effect of high voltage, the maximum deflection voltage of the electro-optical deflection should be less than 800V / mm.

[0057] According to the deflection angle of 9.6 mrad of the SBN crystal at 800 V voltage, we can calculate its deflection efficiency to be 12 μrad / V, which is nearly two orders of magnitude higher than the deflection efficiency of 0.312urad / V of the deflector with a four-electrode structure proposed by Zhao Zhuo et al. in the background technology.

[0058] Example 8: Electro-optical deflection based on SBN composition gradient (using a composition gradient of 0.0012 mm -1 Crystals)

[0059] From the original crystal obtained in Example 2 (after annealing), a wafer with a size of 5.6 mm × 3 mm × 1.5 mm was processed, and its composition gradient was 0.0012 mm -1 , Al+Pt double-layer electrodes were plated on the two (001) surfaces by the method of Example 6, and then the effective Curie temperature was obtained to be Tc=69.4°C by measuring its dielectric temperature spectrum. The crystal temperature was controlled to 5 degrees below the Curie point, i.e., 64.4°C, by a TEC temperature control device. The other test conditions and methods were the same as those of Example 7. According to the measurement results, the maximum deflection angle was calculated to be 6.5 mrad (@760 V / mm at the maximum deflection voltage).

[0060] Example 9: Electro-optical deflection based on SBN composition gradient (using a composition gradient of 0.001 mm -1 Crystals)

[0061] From the original crystal obtained in Example 3 (after annealing), a wafer with a size of 6 mm × 3 mm × 2.2 mm was processed, and its composition gradient was 0.001 mm -1 , Ti+Au double-layer electrodes are plated on the two (001) surfaces by the method of Example 6, and then the effective Curie temperature is obtained by measuring its dielectric temperature spectrum to be Tc=58.1°C. The crystal temperature is controlled at 3 degrees below the Curie point, i.e., 55.1°C, by a TEC temperature control device. The other test conditions and methods are the same as those of Example 7. According to the measurement results, it can be calculated that the maximum deflection angle is 2mrad (@720V / mm at the maximum deflection voltage).

[0062] Example 10: Experimental verification of the electro-optical effect type of unpolarized SBN crystal

[0063] Structurally, the tetragonal SBN crystal is a ferroelectric phase with a 4mm point group. It is generally believed that the electro-optic effect of the four-directional SBN crystal manifests as a linear electro-optic effect. However, due to the existence of ferroelectric domains, the crystal usually needs to be polarized to obtain a crystal with a large linear electro-optic coefficient. High-voltage polarization is also a routine operation for most crystals with ferroelectric domains (such as lithium niobate, etc.) before they are used as electro-optic crystals. Since the electro-optic effect of unpolarized ferroelectric crystals is usually not obvious, the electro-optical properties before polarization are usually not paid attention to. However, we found a relatively obvious electro-optical deflection on the unpolarized SBN crystal. In order to further prove that this effect is a secondary electro-optic effect rather than a linear electro-optic effect, we used the electro-optic modulation characteristics of the SBN crystal to build a Mach-Zehnder interferometry system ( Fig.12 ), by comparing the frequency relationship between the input voltage signal and the output modulation signal, it is determined whether the deflection is caused by the linear electro-optic effect or the quadratic electro-optic effect.

[0064] exist Fig.12 In the experiment, the laser beam is divided into two beams after passing through the beam splitter 1. One beam of light is phase-delayed by the crystal, and interferes with the other beam of light at the beam splitter 2. The voltage applied to the SBN crystal is changed, and the interference fringes change from bright to dark. The midpoint of the bright and dark fringes is taken as the observation point. In the experiment, a signal generator is used to output a small signal AC voltage of a certain frequency, which is applied to the crystal through a high-voltage amplifier. The intensity of the interference light obtained after passing through BS2 can be recorded by an oscilloscope together with the signal output by the signal generator after passing through a photoelectric detector. According to the conclusion given by Aillerie.M et al. (Aillerie M, Theofanous N, Fontana M D. Measurement of the electro-optic coefficients: description and comparison of the experimental techniques [J]. Applied Physics B, 2000, 70: 317-334), if the crystal exhibits a secondary electro-optic effect, the waveform of the output light intensity recorded by the photoelectric detector and the change relationship of the applied voltage (i.e., the voltage applied to the crystal after the signal output by the signal generator is amplified) follow the following formula:

[0065]

[0066] It can be seen that the interference light intensity under the secondary electro-optical effect is proportional to the square of the voltage.

[0067] If the crystal exhibits a linear electro-optic effect, then: v out ∝E, (2)

[0068] That is, the interference light intensity under the linear electro-optical effect is proportional to the voltage.

[0069] Fig.13 The waveforms of the applied voltage and interference light intensity recorded by the oscilloscope. According to formulas (1) and (2), if the frequencies of the two waveforms are equal, it should be a linear electro-optic effect; if the waveforms show a frequency doubling relationship, it is a quadratic electro-optic effect. Fig.13 It can be seen that the waveform of the output light intensity recorded by the photodetector shows a frequency doubling relationship with the external voltage waveform (i.e., the signal generator waveform) (i.e., the frequency is doubled and the period is halved), proving that the unpolarized SBN crystal used here has a secondary electro-optical effect.

[0070] Comparative Example 1: Comparison of the deflection angles of electro-optical deflection based on the linear electro-optic effect of SBN crystal and electro-optical deflection based on its quadratic electro-optic effect (theory combined with experiment)

[0071] We mentioned in the previous Example 8 that "when the secondary electro-optic effect of the SBN crystal is transformed into a linear electro-optic effect, the electro-optic deflection angle will be attenuated", which is what we Fig.11 Based on the conclusions inferred from the experimental results, we will deduce and calculate the deflection angles of these two deflections theoretically:

[0072] We know that when a light beam propagates in an inhomogeneous medium, it always bends in the direction of increasing refractive index, such as Fig.14 When the light beam enters the crystal along the x direction, due to the component gradient in the z direction, there will be a deflection angle θ0 (defined as intrinsic deflection) even without applying voltage. According to the theory of refractive index gradient by AF Dugan et al. (Dugan AF, Doyle WM, Sutton PM. KTN concentration gradient light beam deflector [J]. Applied Optics, 1968, 7 (3): 556-1-558.), the relationship between the intrinsic deflection angle θ0 and the refractive index gradient can be expressed as:

[0073]

[0074] Where L is the length of the crystal in the direction of beam propagation, is the refractive index gradient of the crystal at any position z,

[0075] When an external voltage is applied to the crystal, the crystal will produce a change in refractive index due to the electro-optic effect. If the crystal exhibits a secondary electro-optic effect, the refractive index change can be expressed as

[0076]

[0077] Among them, n(z), s ij (z) represent the refractive index and the secondary electro-optic coefficient of the crystal at any position z without voltage applied, and E is the electric field intensity.

[0078] At this time, the beam deflection angle Δθ caused by the applied voltage can be expressed as ( Fig.13 )

[0079]

[0080] Substituting (4) into (5) we can obtain, and replacing E with Indicates that

[0081]

[0082] If used separately and represents the refractive index gradient and electro-optic coefficient gradient of the crystal along the growth direction. When the polarization direction of the incident light is parallel to the electric field direction, the refractive index and secondary electro-optic coefficient at any position in the crystal can be expressed as,

[0083] n(z)=n0-n'z (7)

[0084] s ij (z) = s 11 -s'z (8)

[0085] Where n0 is the refractive index of extraordinary light at z = 0, s 11 is the secondary electro-optic coefficient at z=0.

[0086] Therefore, substituting (7) and (8) into (6) we obtain

[0087]

[0088] Among them, the term (n0-n'z) and (s 11 -s'z) respectively represent the refractive index and the secondary electro-optic coefficient at different positions inside the crystal when no electric field is applied. When involved in the calculation in equation (9), since n'z = n0, s'z = s 11 , so these two terms can be approximately expressed as (n0-n'z)≈n0, (s 11 -s'z)≈s 11 , so (9) can be written as

[0089]

[0090] According to equation (10), to calculate the angle of electro-optical deflection, we need to know the refractive index n0 and the secondary electro-optic coefficient s at z = 0. 11 , as well as the refractive index gradient and quadratic electro-optic coefficient gradient of the crystal along the z direction.

[0091] For the calculation of the secondary electro-optic coefficient, we start from Figure 3 (a) Two 1×1×1 mm wafers were cut from the upper and lower parts of the crystal. Fig.12 The Mach-Zehnder interferometer shown in the figure measures the secondary electro-optic coefficient and calculates the gradient value of the secondary electro-optic coefficient, s' = 2 × 10 -15 m / v 2 , in which we approximate the refractive index gradient of the large crystal to be the same as that of the small crystal.

[0092] For the calculation of the refractive index gradient, we used the method of Tunyagi A R. et al. (Tunyagi A R. Non-Collinear second harmonic generation in strontium barium niobate [J]. Unpublished doctoral dissertation, The Sellmeier equation for calculating the refractive index is given by Osnabrück, Osnabrück, Germany, 2004.

[0093]

[0094] Among them, the four coefficients A, B, C, and D of the Sellmeier equation are related to the component x of SBN:

[0095]

[0096] The wavelength of the incident light is λ = 632.8 nm, measured by EPMA-8050G Figure 8 (b) The upper and lower surfaces and the middle position of the crystal ( Fig.13 The components at z = 0 are 0.6410, 0.6395, and 0.6403, respectively. The corresponding refractive indices calculated by equation (11) are 2.3036, 2.3034, and 2.3035, respectively. Therefore, the refractive index gradient of the crystal is n' = 1 × 10 -4 / mm, therefore, substituting the above data into formula (10), we can obtain the theoretical curve of the electro-optical deflection angle changing with the applied voltage, as shown in Fig.11As shown by the upper solid line, when the voltage is less than 800V, the change trend of the curve obtained by theoretical calculation is basically consistent with the experimental results. Both increase with the increase of voltage in a parabolic law. When the voltage is greater than 800V, the theoretical curve deviates from the experimental results. This is due to the polarization effect of high voltage on the internal domain structure of the crystal.

[0097] In order to further determine the influence of high voltage polarization on the electro-optical effect of SBN, we conducted Figure 8 The crystal in (b) was polarized using a single-channel polarizer (BALAB SPD10KV) at 9KV / cm DC electric field at 3°C ​​above the Curie temperature for 30 minutes, and then slowly cooled to room temperature to prepare a single-domain SBN crystal. Fig.11 The Mach-Zehnder experimental device shown in the figure observes the change of interference light intensity to the applied voltage and finds that the frequency doubling phenomenon disappears. The two show the same periodic change law, proving that this is the linear electro-optic effect. That is, when the applied voltage causes the tetragonal SBN crystal to change from the disordered state of domain structure orientation to the single domain state, the crystal also changes from the secondary electro-optic effect to the linear electro-optic effect.

[0098] Then we also theoretically derived the expression of the electro-optical deflection angle based on the linear electro-optic effect (the method is similar to the derivation method of formula (10)):

[0099]

[0100] Among them, γ 33 represents the linear electro-optic coefficient of the crystal at z = 0, γ' represents the linear electro-optic coefficient gradient, and γ 33 and γ' take typical values, referring to the linear electro-optic coefficient values ​​γ of different components that have been measured in relevant literature 33 =520pm / v,γ'=9×10 -12 / v, and substituting it into (13), when the applied voltage is 800V, the electro-optical deflection angle caused by the linear electro-optical effect is 0.018mrad, which is much smaller than the deflection angle (9.6mrad) caused by the secondary electro-optical effect in Example 1. This proves that the deflection of the unpolarized SBN crystal at low voltage is mainly caused by the secondary electro-optical effect of the crystal, and also proves that the decrease in the deflection angle at high voltage is caused by the transformation of the crystal from the secondary electro-optical effect to the linear electro-optical effect.

Claims

1. A light deflection method based on barium strontium niobate crystals with gradient composition, characterized in that: The method comprises the following steps: (1) Using the Czochralski method to grow Sr x Ba 1-x Nb2O6 crystals, the molar ratio range of the initial raw materials is: 0.65:0.35 < SrCO3:BaCO3 < 0.79:0.21, and the component gradient of the crystal along the growth direction, i.e., the [001] direction, should be greater than 10 -3 / mm; (2) The SBN crystal with composition gradient is processed into a cuboid wafer and optically polished, and each surface corresponds to the (100), (010) and (001) planes of the crystal, respectively. A double-layer metal electrode is plated on the two (001) planes, wherein the electrode material of the inner layer in contact with the crystal is one of Al, Ti or Ag, and the electrode material of the outer layer in contact with the air is one of Au or Pt, and the electrode and the crystal should form an ohmic contact; (3) The incident light is perpendicular to the (100) or (010) plane of the crystal. A polarizer is used to convert the incident light into linearly polarized light polarized along the [001] direction before the light beam enters the crystal. An electric field is applied to the SBN crystal along the [001] direction, and the light beam can be deflected at the crystal output end.

2. The light deflection method based on barium strontium niobate crystal with gradient composition according to claim 1, characterized in that: When the SBN crystal is used as an electro-optical deflection element, its temperature is controlled within a range of 3 to 5° C. below the effective Curie temperature.

3. The light deflection method based on barium strontium niobate crystal with gradient composition according to claim 1, characterized in that: The SBN crystal grown by the Czochralski method needs to be annealed in a high-temperature oxygen atmosphere at a temperature of 1200°C-1300°C, a constant temperature time of 12-24 hours, and a heating and cooling rate of 100-200°C / h.

4. The light deflection method based on barium strontium niobate crystal with gradient composition according to claim 1, characterized in that: The SBN crystal is in a tetragonal phase and cannot be subjected to high-voltage polarization treatment when used for electro-optical deflection.

5. The light deflection method based on barium strontium niobate crystal with gradient composition according to claim 1, characterized in that: The maximum deflection voltage applied to the SBN crystal should be less than 800V / mm.

6. The light deflection method based on barium strontium niobate crystal with gradient composition according to claim 1, characterized in that: The double-layer metal electrodes are coated on the surface by magnetron sputtering, the thickness of the inner electrode is 50-150nm, and the thickness of the outer electrode is 100-200nm.

7. The light deflection method based on barium strontium niobate crystal with gradient composition according to claim 1, characterized in that: After the metal electrode is sputtered, it needs to be rapidly annealed. The annealing temperature is 300-500°C, the constant temperature time is 5-10 minutes, the heating time is 5-30 seconds, and the annealing atmosphere is nitrogen or argon.

8. An electro-optical deflection device prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A lidar 3D scanning rotating mirror system

    CN104749565B

  • A layered acousto-optic deflector and a method for deflecting a light beam using such a deflector.

    CN107850796B

  • A MEMS scanning lidar and scanning method

    CN109085600B

  • A large-aperture, low-driving-voltage two-dimensional electro-optic deflection device

    CN110543035B

  • A 3D scanning lidar based on MEMS galvanometers

    CN111289955B